Orientation imaging of macro-sized polysilicon grains on wafers using spatially resolved acoustic spectroscopy - Patel, Rikesh; Li, Wenqi; Smith, Richard J.; Sharples, Steve D.; Clark, Matt (Elsevier, 2017)
Due to its economical production process polysilicon, or multicrystalline silicon, is widely used to produce solar cell wafers. However, the conversion efficiencies are often lower than equivalent monocrystalline or thin film cells, with the structure and orientation of the silicon grains strongly linked to the efficiency. We present a non-destructive laser ultrasonic inspection technique, capable of characterising large (52 x 76 mm2) photocell's microstructure – measurement times, sample surface preparation and system upgrades for silicon scanning are discussed. This system, known as spatially resolved acoustic spectroscopy (SRAS) could be used to optimise the polysilicon wafer production process and potentially improve efficiency.